MELECON 2006 - 2006 IEEE Mediterranean Electrotechnical Conference
DOI: 10.1109/melcon.2006.1653318
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Insulating Barriers on AC Breakdown Voltage in Inhomogeneous Field

Abstract: In this study, the effect of insulating barriers on the breakdown voltage of air in inhomogeneous field is observed. Tests are conducted in order to measure the 50 Hz AC breakdown voltage of small air gaps (up to 50 mm) formed by hemispherically capped rod-plane electrodes with an insulating barrier between them. Energized rod and grounded plane gaps are studied with the flat insulating barriers that have three different diameters. The results of the test series show how the breakdown voltage varies with the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…The polarization of the water establishes a dielectric permittivity gradient which further focuses the electric field by the action of dielectric saturation 40 whereby the effective electric field strength is increased due to space charge effects induced by the dielectric medium. 41, 42 The observed changes in the Raman cross section (Fig. 7) are reflective of the development of this space charge and can be thought to be similar to the onset of charge density wave effects observed in solid state materials 43,44 .…”
Section: The Effect Of Exciting a Delocalized Vibrational Statementioning
confidence: 61%
“…The polarization of the water establishes a dielectric permittivity gradient which further focuses the electric field by the action of dielectric saturation 40 whereby the effective electric field strength is increased due to space charge effects induced by the dielectric medium. 41, 42 The observed changes in the Raman cross section (Fig. 7) are reflective of the development of this space charge and can be thought to be similar to the onset of charge density wave effects observed in solid state materials 43,44 .…”
Section: The Effect Of Exciting a Delocalized Vibrational Statementioning
confidence: 61%
“…For studies on the high voltage breakdown characteristics of gases, applications of low frequency AC or DC are commonly considered as an electrostatic field problem and calculations are made on the basis of static field concepts (Chankuson & Nisoa, 2021; Kara et al, 2006; M'ziou et al, 2018). In the present study, a DC stationary study and an AC time‐dependent study were performed separately to manifest the difference.…”
Section: Discussionmentioning
confidence: 99%
“…The simulation was conducted in COMSOL Multiphysics software (version 5.6, COMSOL, Inc., Burlington, MA, USA). This software and the underlying physics have been used to simulate electric filed for plasma generation and breakdown characteristics of gases (Chankuson & Nisoa, 2021; Kara et al, 2006; M'ziou et al, 2018). We used COMSOL AC/DC Module in the mode of stationary electric currents for the first case under a stationary high voltage DC, and the mode of time‐dependent electric currents for the second case under a high voltage AC to describe the electric field distribution.…”
Section: Methodsmentioning
confidence: 99%
“…The effect is widely applied in HV equipment design with a standard needle-plane electrode configuration to enhance the breakdown strength. Preliminary studies by Marx and Rozer reported the role of enhanced withstand strength due to barriers during the discharge studies in air gaps irrespective of the dielectric medium's phase (liquid, gaseous, or solid), voltage type (DC, AC power frequency or Lightning Impulse (LI) and Switching Impulse (SI)) [5], configuration of electrode (needle-plane or plane-plane configuration) and inter-electrode distance of air gap (short, medium and long gaps). Though many experimental studies [6] have been carried out to address this problem, the barrier effect mechanism is yet to be completely understood comprehensively.…”
Section: Figure 1 Plot Of Breakdown Voltage and Frequencymentioning
confidence: 99%